Combined Effect of Slip Velocity and Roughness on the Jenkins Model Based Ferrofluid Lubrication of a Curved Rough Annular Squeeze Film - JIMITKUMAR PATEL; G. M. Deheri (Journal of Applied Fluid Mechanics, 2016)
This paper theoretically analyzes the combined effect of slip velocity and surface roughness on the performance of Jenkins model based ferrofluid squeeze film in curved annular plates. The effect of slip velocity has been studied resorting to the slip model of Beavers and Joseph. The stochastically averaging method of Christensen and Tonders has been deployed for studying the effect of surface roughness. The pressure distribution is derived by solving the associated stochastically averaged Reynolds type equation with suitable boundary conditions, leading to the computation of load carrying capacity. The graphical representations reveal that the transverse surface roughness adversely affects the bearing performance. However, Jenkins model based ferrofluid lubrication offers some scopes in minimizing this adverse effect when the slip parameter is kept at minimum. Of course, an appropriate choice of curvature parameters adds to this positive effect in the case of negatively skewed roughness. Moreover, it is established that this type of bearing system supports certain amount of load; even when there is no flow which does not happen in the case of conventional lubricant based bearing system.